2014
DOI: 10.4103/2303-9027.144530
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating primary pancreatic lymphoma from adenocarcinoma using endoscopic ultrasound characteristics and flow cytometry: A case-control study

Abstract: Background:Primary pancreatic lymphoma (PPL) is a rare pancreatic neoplasm that is difficult to diagnose. PPL has a vastly different prognosis and treatment regimen than other pancreatic tumors; therefore, accurate diagnosis is vital. In this article, we describe the characteristic presentation, endoscopic ultrasound (EUS) features, and the role of fine-needle aspiration (FNA) in the diagnosis of PPL compared with pancreatic adenocarcinoma.Materials and Methods:This was a retrospective case-control study of 11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 14 publications
0
18
0
Order By: Relevance
“…[ 2 6 7 8 9 ] The key EUS feature that can differentiate plasmacytomas from pancreatic adenocarcinoma is the well-defined margin of the tumor. [ 10 11 ] A pancreatic neuroendocrine tumor presents as a round, homogeneous, hypo- or isoechoic mass on EUS. [ 12 ] Plasmacytomas of the pancreas usually show a more uneven margin and more heterogeneous echogenicity than neuroendocrine tumors.…”
Section: Discussionmentioning
confidence: 99%
“…[ 2 6 7 8 9 ] The key EUS feature that can differentiate plasmacytomas from pancreatic adenocarcinoma is the well-defined margin of the tumor. [ 10 11 ] A pancreatic neuroendocrine tumor presents as a round, homogeneous, hypo- or isoechoic mass on EUS. [ 12 ] Plasmacytomas of the pancreas usually show a more uneven margin and more heterogeneous echogenicity than neuroendocrine tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that a combination of FC and other ancillary studies increase the sensitivity and specificity. The diagnostic accuracy is particularly improved with the addition of FC [62,63]. …”
Section: Fna Diagnosis Of Specific Organ-based Primary Deep-seated Lymentioning
confidence: 99%
“…Despite the larger size at presentation, it is less likely to be associated with pancreatic duct dilation and vascular invasion [62,63]. Malignant-appearing lymphadenopathy is significantly more common in PPLs than in adenocarcinomas [62]. Similar to lymphomas elsewhere, the most important cytomorphological clue to the diagnosis is a cellular aspirate with mostly dyshesive cells with scant cytoplasm and associated with abundant lymphoglandular bodies.…”
Section: Fna Diagnosis Of Specific Organ-based Primary Deep-seated Lymentioning
confidence: 99%
See 2 more Smart Citations